Populism and crisis politics in greece - Pappas, Takis S.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Exploring the negative effects of populism, this study presents an original explanation of Greece's current political and economic failures. It argues that the sovereign debt crisis only exacerbated the malfunctioning of a democracy long ago contaminated by populist politics while also offering a more general insight into the impact of populism.
Keywords: Science; Science, general